Analisis Rekonsiliasi Fiskal Dan Perhitungan Pph Badan Pada PT XXX Tahun 2018 - Adeline Michaella, Purnamawati Helen Widjaja (Fakultas Ekonomi, Universitas Tarumanagara, 2021)
The research aims to know if fiscal reconciliation, the calculation of income tax and the calculation of tax installment art. 25 matched to the law of tax in Indonesia especially the law of the Republic of Indonesia No. 36 of 2008. This research is a descriptive study with surveyed to PT XXX directly. Data that used in this research is quantitative data such as commercial financial statement, fiscal financial statement, and company fiscal reconcilliation statement. The result of this research shows that fiscal correction conducted by PT XXX is not matched with the tax regulation, so that affect the calculation of income tax and tax installment art. 25 that had been already paid and reported.